Interval exchange dynamics and wandering intervals - Cundari, Guilherme Zahra [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
Este trabalho tem como objetivo apresentar os conceitos e resultados necessários para a compreensão de um resultado sobre sistemas dinâmicos relacionados a intercâmbios de intervalos. Mais precisamente, se T é um intercâmbio de intervalos autossimilar com \theta_1 autovalor de Perron-Frobenius da matriz associada ao loop da indução de Rauzy sobre T e existe um autovalor real \theta_2 conjugado a \theta_1 tal que \theta_2>1, então existe um intercâmbio de intervalos afim f, semi-conjugado a T, que possui intervalos errantes. Este resultado foi obtido por X. Bressaud, P. Hubert e A. Maass. Para construir o conhecimento necessário, são estudadas duas áreas principais: a dinâmica de intercâmbios de intervalos e a dinâmica simbólica, destacando as conexões entre essas teorias.

This work aims to present the concepts and results necessary for understanding a result concerning dynamical systems related to interval exchange transformations. More precisely, if T is a self-similar interval exchange transformation with \theta_1 the Perron–Frobenius eigenvalue of the matrix associated with the Rauzy induction loop of T, and if there exists a real eigenvalue \theta_2 conjugate to \theta_1 such that \theta_2>1, then there exists an affine interval exchange transformation f, semi-conjugate to T, that possesses wandering intervals. This result was obtained by X. Bressaud, P. Hubert, and A. Maass. In order to develop the necessary background, two main areas are studied: interval exchange dynamics and symbolic dynamics, emphasizing the connections between these theories.
Dinâmica de intercâmbio de intervalos e intervalos errantes
Keywords: Intercâmbios de intervalos; Dinâmica simbólica; Substituições; Fractal de Rauzy; Intervalos errantes; Interval exchange transformation; Symbolic dynamics; Substitutions; Rauzy fractal; Wandering intervals